(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article focuses on experiments conducted among students with excess body weight and the analysis of their outcomes. The study was carried out in three secondary schools in Andijan province. During the experiments, students’ physical activity, dietary habits, and psychological well-being were examined. The aim of the research is to identify effective approaches to addressing the issue of overweight. The findings contributed to developing recommendations for optimizing physical education programs and promoting a healthy lifestyle.